Digital Transformation in Real Estate Marketing - Sych, Illia (2024)
The purpose of this bachelor's thesis thesis is to develop measures for implementing digital transformation of marketing in a specific real estate agency based on the con-sideration of theoretical aspects of digital transformation of marketing and assess-ment of the conditions of such transformation. The paper used methods of abstracting scientific literature, analyzing the company's reporting, SWOT-analysis, analyzing the dynamics and structure of indicators, etc. The research was conducted in 3 stages, and it was found that the company has a high level of digital maturity (8.3 out of 10), but needs to improve the use of online sources and the introduction of new digital tools. The measures developed are expected to lead to a significant improvement in the company's economic performance, increasing revenue by 14.47% and net profit by €16.1k, as well as increasing digital maturity to 8.7 points.